Kairo, Ägypten. Restaurierungsprojekt Glasnegative im Center of Documentation, Zitadelle Kairo. Die Arbeiten der Jahre 2015 bis 2017 - Mayer, Wolfgang; Ahmed, Nesma; Bartels, Kerstin; Falk, Sebastian (e-Forschungsberichte des DAI, 2017)
The Photographic Archive at the Citadel in Old Cairo / Egypt comprises ca. 14,000 objects, mainly silver gelatine glass negatives and acetate sheet film negatives. Since 2002 the DAI Cairo is – thanks to the support by the German Foreign Ministry – involved in a restauration and training program which aims at helping to secure, safely store, and conserve the glass negatives and at training of local inspectors in order to create local conservation and restauration capacities.